2022
DOI: 10.1088/1674-1056/ac3222
|View full text |Cite
|
Sign up to set email alerts
|

Majorana zero modes, unconventional real–complex transition, and mobility edges in a one-dimensional non-Hermitian quasi-periodic lattice

Abstract: A one-dimensional non-Hermitian quasiperiodic p-wave superconductor without P T -symmetry is studied. By analyzing the spectrum, we discovered that there still exists real–complex energy transition even if the inexistence of P T … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…For example recently, plenty of interesting localization properties have been found in one-dimensional (1D) lattices with a quasi-periodic potential, such as well-defined mobility edges [22,23], and a critical region consisting of critical states [24]. Insightful predictions on other rich physics in 1D quasi-periodic lattices are proposed, for example, topology, non-Hermeticity, superconductivity and superfluidity [25][26][27][28]. Some interesting experimental realizations of quasicrystalline physics have also been discussed recently [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…For example recently, plenty of interesting localization properties have been found in one-dimensional (1D) lattices with a quasi-periodic potential, such as well-defined mobility edges [22,23], and a critical region consisting of critical states [24]. Insightful predictions on other rich physics in 1D quasi-periodic lattices are proposed, for example, topology, non-Hermeticity, superconductivity and superfluidity [25][26][27][28]. Some interesting experimental realizations of quasicrystalline physics have also been discussed recently [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that an intermediate regime characterized by the coexistence of localized and extended states at different energies may occur 3,4 . The theoretical findings were confirmed in an experimental realization of a system with a single-particle mobility edge 5 .Recently, in non-Hermitian systems mobility edges have been explored for various 1D tight-binding models [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . In non-Hermitian systems, in comparison to the Hermitian ones, the mobility edges not only separate localized states from the extended states but also indicate the coexistence of complex and real energies.…”
mentioning
confidence: 68%
“…Recently, in non-Hermitian systems mobility edges have been explored for various 1D tight-binding models [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . In non-Hermitian systems, in comparison to the Hermitian ones, the mobility edges not only separate localized states from the extended states but also indicate the coexistence of complex and real energies.…”
mentioning
confidence: 99%